Childhood obesity and comorbidities-related perspective and experience of parents from Black and Asian minority ethnicities in England: a qualitative study - Obita, George; Burns, Mark; Nnyanzi, Lawrence Achilles; Kuo, Chia-Hua; Barengo, Noël C.; Alkhatib, Ahmad (Frontiers in Public Health, 2024)
We are pleased to submit the manuscript "Childhood Obesity and comorbidities-related perspective and experience of parents from Black and Asian Minority Ethnicities in England; a Qualitative Study". Childhood obesity and associated comorbidities are an important global public health concern, and so it is important to address prevention in high-risk ethnic minority communities through this qualitative research. The study contextualises factors influencing childhood obesity and related comorbidity and pave the way to better inform healthcare preventative interventions, especially lifestyle physical activity and nutrition interventions, associated healthcare policies for high-risk minority ethnic populations. It contributes to matching the government childhood obesity prevention programmes with the perceptions and needs of high-risk ethnic minority communities so that obesity prevention in minority ethnicities are more equitable.